BIOTECHNOLOGICAL BASES OF A FUNCTIONAL DRINK BASED ON WHEY - I. S. Rodionov; I. A. Evdokimov; E. A. Abakumova (Современная наука и инновации, 2023)
The relevance of obtaining whey after enzymatic hydrolysis for various types of functional drinks is substantiated. A comparative analysis of the enzymatic activity of different enzymes was carried out, and a composition of a functional drink was developed.